Diabetology 4.0: Scoping Review of Novel Insights and Possibilities Offered by Digitalization - Eberle, Claudia; Stichling, Stefanie; Löhnert, Maxine (JMIR Publications, 2021)
BackgroundThe increasing prevalence of diabetes mellitus and associated morbidity worldwide justifies the need to create new approaches and strategies for diabetes therapy. Therefore, the ongoing digitalization offers novel opportunities in this field. ObjectiveThe aim of this study is to provide an updated overview of available technologies, possibilities, and novel insights into diabetes therapy 4.0. MethodsA scoping review was carried out, and a literature search was performed using electronic databases (MEDLINE [PubMed], Cochrane Library, Embase, CINAHL, and Web of Science). The results were categorized according to the type of technology presented. ResultsDifferent types of technology (eg, glucose monitoring systems, insulin pens, insulin pumps, closed-loop systems, mobile health apps, telemedicine, and electronic medical records) may help to improve diabetes treatment. These improvements primarily affect glycemic control. However, they may also help in increasing the autonomy and quality of life of people who are diagnosed with diabetes mellitus. ConclusionsDiabetes technologies have developed rapidly over the last few years and offer novel insights into diabetes therapy and a chance to improve and individualize diabetes treatment. Challenges that need to be addressed in the following years relate to data security, interoperability, and the development of standards.